Transcriptome-wide expression analysis of MYB gene family leads to functional characterization of flavonoid biosynthesis in fruit coloration of Ziziphus Mill - Muhammad, Noor; Luo, Zhi; Zhao, Xin; Yang, Meng; Liu, Zhiguo; Liu, Mengjun (Frontiers in Plant Science, 2023)
The Ziziphus mauritiana Lam. and Z. jujuba Mill. are the two most economically important members of the genus Ziziphus. The fruit color of Z. mauritiana remains green throughout fruit development in the majority of commercial cultivars, whereas its close relative, Z. jujuba Mill. turns from green to red in all cultivars. However, the lack of transcriptomic and genomic information confines our understanding of the molecular mechanisms underlying fruit coloration in Z. mauritiana (Ber). In the present study, we performed the transcriptome-wide analysis of MYB transcription factors (TFs) genes in Z. mauritiana and Z. jujuba, and identified 56 ZmMYB and 60 ZjMYB TFs in Z. mauritiana and Z. jujuba, respectively. Through transcriptomic expression analysis, four similar MYB genes (ZmMYB/ZjMYB13, ZmMYB/ZjMYB44, ZmMYB/ZjMYB50, and ZmMYB/ZjMYB56) from Z. mauritiana and Z. jujuba were selected as candidate key genes regulating flavonoid biosynthesis. Among these genes, the ZjMYB44 gene was transiently highly expressed in fruit, and flavonoid content accumulation also increased, indicating that this gene can influence flavonoid content during the period of fruit coloration in Z. jujuba. The current study adds to our understanding of the classification of genes, motif structure, and predicted functions of the MYB TFs, as well as identifying MYBs that regulate flavonoid biosynthesis in Ziziphus (Z. mauritiana and Z. jujuba). Based on this information, we concluded that MYB44 is involved in the flavonoids biosynthesis pathway during the fruit coloring of Ziziphus. Our research results provide an important understanding of the molecular mechanism of flavonoid biosynthesis resulting in fruit coloration and laying a foundation for further genetic improvement of fruit color in Ziziphus.